Antimicrobial Activity of Medicinal Compounds Produced by Fungal Degradation of Soybean Oil Using Lignocellulose Biomass as Surface (Journal of Basic and Applied Research in Biomedicine, 2022)
Methyl esters were produced by fungal degradation of soybean oil using banana leaves as surface. Analysis of the products also revealed medicinal compounds (Benzyl Benzoate obtained from the banana leaves used as surface for the fungal degradation of the soybean oil and 1, 2-Benzene dicarboxylic acid dioctyl ester obtained from the soybean oil impurities). Microorganism activity test was carried out on the medicinal compounds to confirm their antibacterial and antifungal activity. The result showed that both had antibacterial and antifungal activity as shown by the zones of inhibition and as a result can find useful applications in food processing and preservation as well as agriculture as pest/disease control agents.